2021
DOI: 10.3390/su13169163
|View full text |Cite
|
Sign up to set email alerts
|

Reading Urban Green Morphology to Enhance Urban Resilience: A Case Study of Six Southern European Cities

Abstract: A loss of natural capital within cities and their surrounding areas has been noticed over the last decades. Increasing development associated with higher sealing rates has caused a general loss of Urban Green Spaces (UGS) within the urban environment, whereas urban sprawl and the improvement of road networks have deeply fragmented the surrounding landscape and jeopardized ecosystems connectivity. UGS are an essential component of the urban system, and their loss has a greater impact on, e.g., ecological and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Rapid urbanisation, coupled with piecemeal planning and the development of informal settlements, have caused the diminishing of green spaces in Mlandizi town. Urban green spaces are very important for urban landscapes in providing ecosystem services, including biodiversity support, as well as water and temperature regulation (Pezzagno et. al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Rapid urbanisation, coupled with piecemeal planning and the development of informal settlements, have caused the diminishing of green spaces in Mlandizi town. Urban green spaces are very important for urban landscapes in providing ecosystem services, including biodiversity support, as well as water and temperature regulation (Pezzagno et. al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study of six historic city centres in Southern Europe identified three main patterns of urban green, namely, fragmented, compact and linear distribution, with corresponding implications for the potential provision of ecosystem services. As can be seen from the published map sections, all the study sites are essentially located within urban core areas, corresponding to the urban mask [17].…”
Section: Introduction and State Of Researchmentioning
confidence: 99%
“…Urbanization in Europe has been relatively well studied, despite important differences at the regional scale [15][16][17]. It is probable that the less studied urbanization processes came from Socialist countries in Eastern Europe, where urbanization was strictly planned in the aftermath of World War II, under substantially different conditions (e.g., property regimes) compared with Western Europe [18][19][20][21][22]. In this sense, the relationship between urbanization and the environment in Eastern Europe has been poorly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Achieving these benefits requires careful consideration of several key aspects covering a wide range of scientific fields, from environmental psychology to ecosystem engineering and ecological education [40]. Despite the increasing acknowledgement of the benefits of and the need for urban green and blue areas by several international organizations, such as the United Nations [41] and the European Commission [42], over the last few years, urbanization has resulted in their fragmentation and decreasing extent [22].…”
Section: Introductionmentioning
confidence: 99%